The Me31B DEAD-Box Helicase Localizes to Postsynaptic Foci and Regulates Expression of a CaMKII Reporter mRNA in Dendrites of Drosophila Olfactory Projection Neurons. - Hillebrand, J.; Pan, K.; Kokaram, A.; Barbee, S.; Parker, R.; Ramaswami, M. (Frontiers in neural circuits, 2010)
mRNP granules at adult central synapses are postulated to regulate local mRNA translation and synapse plasticity. However, they are very poorly characterized in vivo. Here, in Drosophila olfactory synapses, we present early observations and characterization of candidate synaptic mRNP particles, one of which contains a widely conserved, DEAD-box helicase, Me31B. In Drosophila, Me31B is required for translational repression of maternal and miRNA-target mRNAs. A role in neuronal translational control is primarily suggested by Me31B's localization, in cultured primary neurons, to neuritic mRNP granules that contain: (i) various translational regulators; (ii) CaMKII mRNA; and (iii) several P-body markers including the mRNA hydrolases, Dcp1, and Pcm/Xrn-1. In adult neurons, Me31B localizes to P-body like cytoplasmic foci/particles in neuronal soma. In addition it is present to synaptic foci that may lack RNA degradative enzymes and localize predominantly to dendritic elements of olfactory sensory and projection neurons (PNs). MARCM clones of PNs mutant for Me31B show loss of both Me31B and Dcp1-positive dendritic puncta, suggesting potential interactions between these granule types. In PNs, expression of validated hairpin-RNAi constructs against Me31B causes visible knockdown of endogenous protein, as assessed by the brightness and number of Me31B puncta. Knockdown of Me31B also causes a substantial elevation in observed levels of a translational reporter of CaMKII, a postsynaptic protein whose mRNA has been shown to be localized to PN dendrites and to be translationally regulated, at least in part through the miRNA pathway. Thus, neuronal Me31B is present in dendritic particles in vivo and is required for repression of a translationally regulated synaptic mRNA.